THU0063 Serum Progranulin Levels are Elevated in Dermatomyositis Patients with Acute Interstitial Lung Disease, Reflecting Severity and Prognosis. (23rd January 2014) - Tanaka, A.; Tsukamoto, H.; Ueda, N.; Ayano, M.; Ohta, S.-I.; Ueki, N.; Ueda, S.; Hisamoto, S.; Oryoji, D.; Hirosaki, Y.; Akahoshi, M.; Arinobu, Y.; et al.
Abstract : Background: Recently, it has been reported that granulin (GRN) and/or progranulin (PGRN), precursor of GRN, is a soluble cofactor for TLR9 signaling [1 ]. We reported that serum PGRN levels are associated with SLE global activity and PGRN may have a role in the pathogenesis via increased cytokine production [2 ]. TLR9 is also involved in the pathological condition of dermatomyositis (DM). Moreover, DM is occasionally complicated with interstitial lung disease (ILD). However, the roles of PGRN and GRN in DM are still unknown. Objectives: To determine if serum PGRN levels are elevated in DM patients, in particular, complicated with ILD and are associated with severity and prognosis. Methods: The serum levels of PGRN were measured by ELISA in patients with DM (n=50; acute/subacute interstitial pneumonia (A/SIP), defined as a rapidly progressive ILD within 3 months from the onset of symptoms: n=13, chronic interstitial pneumonia (CIP): n=20, without ILD: n=17), polymyositis (PM, n=21) and normal healthy controls (NHCs, n=60). We assessed the correlation between the serum PGRN levels and the activity indexes of ILD. The sera from some of the patients were reevaluated after the disease was ameliorated by treatment (n=6). Moreover, we calculated the cumulative survival rate for 6 months in DM patients with ILD, which is classified two groups, serum PGRN levels > or =200 ng/ml and < 200 ng/ml. Results: The serum PGRN levels were significantly higher in the DM patients (median: 100 ng/ml) than in the PM patients (60.4 ng/ml, P=0.0028) and NHCs (48.3 ng/ml, P<0.0001). Of the total DM patients, the levels were significantly higher in DM with A/SIP than that in DM with CIP (P<0.0001) or without ILD (P=0.0002). Proportion of clinically amyopathic DM is higher in DM with A/SIP than in DM with CIP or without ILD (76.9%, 40%, and 5.9%, respectively). The serum PGRN levels correlated significantly with serum ferritin (rs=0.71, P=0.0001), LDH (rs=0.59, P=0.0003), and CRP (rs=0.57, P=0.0005) levels. They significantly decreased following successful treatment of DM (P=0.0313). Moreover, the cumulative survival rate for 6 months was significantly lower in the group with serum PGRN levels > or =200 ng/ml (60%) than that in the group with serum PGRN levels < 200 ng/ml (P=0.001). Conclusions: These findings indicate that PGRN is associated with severity and prognosis of DM with ILD. PGRN may play a role in the pathogenesis of DM by affecting the TLR9 signaling and could be a useful biomarker. References: Park B, Buti L, Lee S, et al. Granulin is a soluble cofactor for toll-like receptor 9 signaling. Immunity 2011;34:505-513. Tanaka A, Tsukamoto H, Mitoma H, et al. Serum progranulin levels are elevated in patients with systemic lupus erythematosus, reflecting disease activity. Arthritis Res Ther 2012;14(6):R244. Disclosure of Interest: None Declared